Pathogen-specific molecular imaging and molecular testing methods in the prognosis of the complicated course of diabetic foot syndrome, the risk of amputation, and patient survival - M. A. Zorkaltsev; V. D. Zavadovskaya; T. V. Saprina; M. A. Zamyshevskaya; V. D. Udodov; A. V. Shestakov; A. A. Mikhailova; Yu. N. Loyko; N. N. Musina (Бюллетень сибирской медицины, 2022)
The aim of this review was to provide extended information on current trends in the diagnosis of complicated diabetic foot syndrome (DFS), the most frequent and severe complication of diabetes mellitus, including hightech medical imaging methods and instrumental and laboratory predictors of the complicated course and risk of amputation in DFS.The article provides an analytical review of modern publications over the past 5 years on diagnosis and therapy. Pilot data on the use of high-tech medical imaging methods, assessment of skin microbiota and ulcers in DFS, molecular testing methods in terms of predicting the amputation risk and survival of patients with DFS, as well as the effectiveness of biosensing systems have been systematized, summarized, and subjected to analytical evaluation.The review provides an expert assessment of the capabilities of pathogen-specific molecular imaging using modern positron emission tomography (PET), single-photon emission computed tomography (SPECT), and highenergy radionuclides in bacterial infection to understand its pathogenesis, minimize diagnostic problems, improve antimicrobial treatment, and address fundamental and applied aspects of DFS. Literature data on the assessment of foot perfusion in diabetic patients with varying degrees of limb ischemia by hybrid technologies (SPECT / CT and PET / CT) and new modalities of magnetic resonance imaging (MRI) are also systematized, which contributes to new understanding of the response to revascularization, surgical shunting, and stimulation of angiogenesis within ischemic tissue, as well as potentially to healing of foot ulcers.The review is aimed at substantiating a multidisciplinary approach in DFS, selection, development, and implementation of innovative strategies for diagnostic modalities to identify diabetic foot pathologies, and choice of an adequate method for treating and monitoring the results of therapy in the context of personalized medicine.